3 x 3 − 3 x 2 + 1 = x
Solve for the value of x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We have 3 x 3 − 3 x 2 + 1 = x . After raising both sides of the equation to the third power it follows that x 3 − 3 x 2 = ( x − 1 ) 3 = x 3 − 3 x 2 + 3 x − 1 . Now we cancel the like terms and we are left with x = 3 1 .
This tells us that if x is a solution to the original equation it must be equal to 3 1 . Substituting x = 3 1 to the original equation yields 3 ( 3 1 ) 3 − 3 ( 3 1 ) 2 + 1 3 2 7 1 − 2 7 9 + 1 3 − 2 7 8 + 1 − 3 2 + 1 3 1 = 3 1 = 3 1 = 3 1 = 3 1 = 3 1 .
Which tells us that x = 3 1 is indeed a solution to the original equation.
Hence the solution is 3 1 .
Here 2nd step is slight wrong..plz correct it.-9/27 is wrong. correct is -1/3
Log in to reply
It isn't wrong. − 2 7 9 is equal to − 3 1 .
-9/27=1/3 usual simplification.
misprint -sign missing
Problem Loading...
Note Loading...
Set Loading...
3 x 3 − 3 x 2 + 1 = x 3 x 3 − 3 x 2 = x − 1 x 3 − 3 x 2 = x 3 − 3 x 2 + 3 x − 1 3 x − 1 = 0 → x = 3 1